Long‐term opioid therapy definitions and predictors: A systematic review. Issue 3 (18th December 2019) - Karmali, Ruchir N.; Bush, Christopher; Raman, Sudha R.; Campbell, Cynthia I.; Skinner, Asheley C.; Roberts, Andrew W.
Abstract: Purpose: This review sought to (a) describe definitions of long‐term opioid therapy (LTOT) outcome measures, and (b) identify the predictors associated with the transition from short‐term opioid use to LTOT for opioid‐naïve individuals. Methods: We conducted a systematic review of the peer‐reviewed literature (January 2007 to July 2018). We included studies examining opioid use for more than 30 days. We classified operationalization of LTOT based on criteria used in the definitions. We extracted LTOT predictors from multivariate models in studies of opioid‐naïve individuals. Results: The search retrieved 5, 221 studies, and 34 studies were included. We extracted 41 unique variations of LTOT definitions. About 36% of definitions required a cumulative duration of opioid use of 3 months. Only 17% of definitions considered consecutive observation periods, 27% used days' supply, and no definitions considered dose. We extracted 76 unique predictors of LTOT from seven studies of opioid‐naïve patients. Common predictors included pre‐existing comorbidities (21.1%), non‐opioid prescription medication use (13.2%), substance use disorders (10.5%), and mental health disorders (10.5%). Conclusions: Most LTOT definitions aligned with the chronic pain definition (pain more than 3 months), and used cumulative duration of opioid use as a criterion, although most did not account for consistent use. Definitions were varied and rarely accounted for prescription characteristics, such as days' supply. Predictors of LTOT were similar to known risk factors of opioid abuse, misuse, and overdose. As LTOT becomes a central component of quality improvement efforts, researchers should incorporate criteria to identify consistent opioid use to build the evidence for safe and appropriate use of prescription opioids.